Our fathers : the secret life of the Catholic Church in an age of scandal - France, David, 1959- (New York : Broadway Books, 2004)
Publisher's description: Our Fathers is history at its best--as intimate as a diary, as immediate and epic as a novel. When, in early 2002, a team of Boston Globe reporters broke open the pedophilia scandal around Father John J. Geoghan--and then Paul Shanley, Joseph Birmingham, and hundreds of other priests in Boston and across the country--the entire American Catholic Church spun into crisis. But by that time, the damage was already done. Perhaps a hundred thousand children had already fallen into traps laid by their priests. Every Catholic in the country--and everyone who had ever set foot in a church--faced troubling questions: Why had this happened? How could the secrets of this abuse have been so widely held, and so closely protected? How could the church have let it happen? David France takes us back to the church of the 1950s, a time of relative innocence, to look for answers. With deft nuance, he crafts a panoramic portrait of the faithful, encompassing the hopes, dreams, disappointments, and courage of hundreds of Catholic and non-Catholic families over the last fifty years. Based on hundreds of interviews, private correspondence, unpublished scientific probes and secret Vatican documents, and tens of thousands of pages of court records, he shows how the church's institutional suspicion of human sexuality ironically lit the fuse on the crisis. Our Fathers braids a heartbreaking narrative from the personal lives of good and bad priests, pious and heartless prelates, self-interested lawyers turned heroes, holy altar boys turned drug-addicts, mothers torn between their children and their faith, hard-bitten investigative reporters reduced to tears, and thousands of church critics who, through this crisis, returned to their faith renewed and invigorated. He shows us the intense history of dissent within the ranks, especially regarding Catholic teachings on sexuality and homosexuality. He tells the heroic stories of whistle-blowing nuns, independent pastors, church insiders trying to do the right thing, and--ultimately--a group of blue-collar men, all molested by the same priest, who overcame their bitterness and took it upon themselves to try to save their church. This book is a tribute to those ordinary Catholics called upon to make extraordinary contributions. Our Fathers is the sweeping, authoritative, and gripping work the scandal and its aftermath demand.
Includes bibliographical references (p. [635]-637) and index.
Keywords: Catholic Church -- Clergy -- Sexual behavior -- United States; Child sexual abuse by clergy -- United States